Survival probabilities and movements of harbor seals in central California. Issue 1 (19th August 2016) - Manugian, Suzanne C.; Greig, Denise; Lee, Derek; Becker, Benjamin H.; Allen, Sarah; Lowry, Mark S.; Harvey, James T.
Abstract: Harbor seal numbers and population trajectories differ by location in central California. Within San Francisco Bay (SFB) counts have been relatively stable since the 1972 Marine Mammal Protection Act, but in coastal areas like Tomales Bay (TB), counts increased before stabilizing in the 1990s. Emigration, poor survival, and environmental effects have been hypothesized as contributors to differences between trajectories; however, basic demographic data were not available to evaluate these hypotheses. We monitored 32 radio‐tagged adult females (SFB n = 17, TB n = 15) for 20 mo (2011–2013), and estimated survival, resight, and movement probabilities using mark‐resight analyses and multistate mark‐resight models. Annual survival probability for both sites was 0.90 (95% CI = 0.18–0.99). Six seals were observed moving between locations resulting in an estimated probability of 0.042 (95% CI = 0.023–0.076) per month equal movement between sites. Resight probability was less in SFB relative to TB, likely due to differential haul‐out access, area surveyed, visibility, and resight effort. Because of wide confidence intervals and low precision of these first estimates of adult female harbor seal survival in California, this demographic must be further examined to dismiss its contribution to differing population trajectories. Using aerial survey data, we estimated 950 harbor seals in SFB (95% CI = 715–1, 184) confirming numbers are still stable.